Characterization of laser cooling in microgravity via long-term operations in TianGong-2 space lab. Issue 4 (29th August 2022) - Lü, De-Sheng; Ren, Wei; Sun, Yuan; Li, Tang; Qu, Qiu-Zhi; Wang, Bin; Li, Lin; Zhao, Jian-Bo; Zhao, Xin; Ji, Jing-Wei; Ye, Mei-Feng; Xiang, Jing-Feng; et al.
Abstract: The invention of laser cooling has fundamentally influenced the research frontier of atomic physics and quantum physics, and recently an intense focus has been on the studies of cold atom physics in microgravity environments. Herein, we report the results of our laser cooling experiment in TianGong-2 space lab, which operated for 34 consecutive months in orbit. Over such an extended operation time, the quality of laser cooling did not experience any significant decline, while the properties of laser cooling in orbital microgravity were systematically studied. In particular, we demonstrate magneto-optical trapping and polarization-gradient cooling in orbit and carefully examine their performances. A comparison of the in-orbit and on-ground results indicates that a higher cooling efficiency exists in microgravity, including a smaller loss rate during the trapping and cooling process and lower ultimate temperature of laser-cooled atoms. Our progress has laid the technical foundations for future applications of cold atoms in space missions with operation times of the order of years. Abstract : Observation of highly efficient laser cooling in microgravity through conducting cold atom experiment in a space lab with successful and consistent performance for almost three years since 2016.